“Ajeg Bali” and Preserving the Balinese Lontar in Dukuh Penaban, Bali - Hapsari, Prima Dona (Institut Seni Indonesia Yogyakarta, 2024)
The necessity to comprehend lontar manuscripts arises from the imperative to preserve the ancestral values of the Balinese people embedded within this medium. The investigation of the lontar manuscript social movement, aimed at cultural preservation within religious rites and as a framework for daily existence (smerti), remains underexplored. This is evidenced by the situation in the Dukuh Penaban Traditional Village, Karangasem, Bali, where few Balinese Hindus have minor thought for which lontar manuscripts are just the sacred things, and possess the ability to read and write lontar manuscripts in Balinese. This represents a novel contribution aimed at addressing a research vacuum that has not been explored by scholars in Indonesia, where an understanding of the social movement, integral to Hindu cultural and religious rites, is necessary. The research necessitates an examination of the Dukuh Penaban Traditional Village community’s response to the legitimacy of the Bali Provincial Government and the preservation initiatives for lontar manuscripts, which have been transmitted through generations. It will reinforce the values of life and the teachings of AJAWERA, ultimately enhancing the character and awareness of the Balinese populace regarding the significance of preserving their esteemed culture. This phenomenon prompts research inquiries on how “Ajeg Bali”, a Balinese society’s discourse to combat globalization, is implemented through cultural preservation actions in the Dukuh Penaban Traditional Village, Karangasem, Bali. This qualitative descriptive research employs an ethnographic methodology, utilizing observation, in-depth interviews, and documentation for data gathering. The research site is Dukuh Penaban Traditional Village, Karangasem Regency, Bali Province. The research participants comprised ten individuals, specifically the Bendesa of Dukuh Penaban Traditional Village, the apparatus of Dukuh Penaban Traditional Village, the Coordinator and members of the Balinese Language Care Alliance of Karangasem Regency, members of the Bebasan Lontar group (readers of lontar manuscripts) from Dukuh Penaban, and Penedun (writers and translators of lontar manuscripts).“Ajeg Bali” and Preserving the Balinese Lontar in Dukuh Penaban, Bali. Munculnya kebutuhan untuk mengetahui dan memahami naskah lontar adalah untuk menyelamatkan nilai-nilai adat warisan leluhur masyarakat Bali yang terkandung dalam media lontar. Riset mengenai gerakan sosial naskah lontar sebagai upaya preservasi budaya sebagai bagian dari ritual keagamaan dan sebagai pedoman kehidupan sehari-hari (smerti) belum banyak dikaji. Hal itu didukung dari fenomena yang ada di Desa Adat Dukuh Penaban, Karangasem, Bali bahwa naskah lontar hanya sebagai benda sakral saja dan belum banyak masyarakat Hindu Bali yang bisa membaca dan menulis naskah lontar dalam Bahasa Bali. Hal ini sekaligus merupakan kebaruan dan digunakan untuk mengisi celah riset yang belum pernah diteliti oleh peneliti di Indonesia, di mana perlu adanya pemahaman akan gerakansosial yang sekaligus menjadi bagian ritual budaya dan agama Hindu. Riset ini perlu untuk diteliti terkait respons masyarakat Desa Adat Dukuh Penaban pada legitimasi Pemerintah Daerah Propinsi Bali serta usaha preservasi naskah lontar yang dimiliki secara turun temurun yang akan menguatkan nilai-nilai hidup dan ajaran AJAWERA yang berdampak pada peningkatan karakter dan kesadaran masyarakat Bali akan pentingnya melakukan pelestarian budaya mereka yang adiluhung. Fenomena tersebut memberi pertanyaan penelitian bagaimana “Ajeg Bali” memberikan wacana masyarakat Bali untuk melawan globalisasi dengan implementasi melalui gerakan sosial pelestarian budaya di Desa Adat Dukuh Penaban, Karangasem, Bali. Penelitian deskriptif kualitatif ini menggunakan pendekatan etnigrafi, dengan metode penelitian yaitu observasi, wawancara mendalam, dan dokumentasi untuk pengumpulan data. Lokasi riset adalah Desa Adat Dukuh Penaban, Kabupaten Karangasem, Propinsi Bali. Informan riset berjumlah 10 orang, yaitu Bendesa Desa Adat Dukuh Penaban, Perangkat Desa Adat Dukuh Penaban, Koordinator dan Anggota Aliansi Peduli Bahasa Bali Kabupaten Karangasem, anggota kelompok Bebasan Lontar (pembaca naskah lontar) Dukuh Penaban, dan Penedun (penulis dan penterjemah naskah lontar).